2017
DOI: 10.1507/endocrj.ej16-0596
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia can be a powerful predictor of the development of isolated ACTH deficiency associated with nivolumab treatment [Letter to the Editor]

Abstract: The report of nivolumab-induced hypophysitis by Okano et al. was of great interest to us [1]. We have experienced four cases of isolated ACTH deficiency after nivolumab administration, suggesting that decreased sodium (Na) concentrations during nivolumab therapy may predict the acute development of isolated ACTH deficiency.The underlying diseases in these four patients were malignant melanoma (case 1) [2] or non-small cell lung carcinoma (cases 2-4) >stage 4 (Table 1). Nivolumab (2 mg/kg, every 3 weeks) was ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 4 publications
4
19
0
Order By: Relevance
“…Unlike the previous case, our case developed adrenal insufficiency after an extremely short period of ACTH elevation with neither subjective symptoms nor Cushing's sign, and there are no published case reports with a similar clinical course. Regarding detection of ICI-induced hypophysitis, we reported that hyponatremia can be a powerful predictor for development of isolated ACTH deficiency associated with nivolumab treatment [12]. Based on the present case, transient ACTH elevation before hyponatremia can be an initial finding for ICI-induced hypophysitis and may be an important finding for early detection of hypophysitis as an irAE.…”
Section: Discussionsupporting
confidence: 49%
“…Unlike the previous case, our case developed adrenal insufficiency after an extremely short period of ACTH elevation with neither subjective symptoms nor Cushing's sign, and there are no published case reports with a similar clinical course. Regarding detection of ICI-induced hypophysitis, we reported that hyponatremia can be a powerful predictor for development of isolated ACTH deficiency associated with nivolumab treatment [12]. Based on the present case, transient ACTH elevation before hyponatremia can be an initial finding for ICI-induced hypophysitis and may be an important finding for early detection of hypophysitis as an irAE.…”
Section: Discussionsupporting
confidence: 49%
“…In IAD, pituitary abnormality was reported to be rarely seen at diagnosis, as was in a case of irAE-related ACTH deficiency (13), and also in our case. Cho et al reported that hyponatremia can be a powerful predictor of the development of isolated ACTH deficiency with nivolumab (14), and our case also showed decrease of serum Na levels from 144 mEq/l to 138 mEq/l in advance of ACTH insufficiency. Ariyasu, et al reported that eosinophilia was observed more than a month before onset of adrenal failure in some cases (6).…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, we describe five cases of adrenal insufficiency attributed to anti-PD1 therapy. In addition, there are 10 previously reported cases of secondary adrenal insufficiency related to anti-PD1 treatment (Table II) (4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%